CONCEPT OF MODERN RESIDENTIAL HOUSES OF BALI ARCHITECTURE IN SUPPORTING ENVIRONMENTAL SUSTAINABILITY - Puguh Idea Triarma; Heru Setiyo Cahyono; Annisa' Carina (DEARSIP : Journal of Architecture and Civil, 2025)
The architecture of the archipelago is rich in cultural values that have been inherited from generation to generation. By adopting local architectural elements into modern designs, we help preserve and preserve Indonesia's cultural heritage. Respect for Local Wisdom: Traditional architecture is designed based on centuries of experience that takes into account the local environmental and cultural conditions. Proud of the Nation's Identity: Showing the architecture of the archipelago in the midst of the era of globalization is a form of appreciation for local wealth that is often forgotten. The typical architecture of the archipelago is rooted in the principle of respecting nature and contextualizing it with the surrounding environment. Traditional houses are often in harmony with the topography, vegetation, and surrounding natural conditions. In the modern context, this can mean maintaining environmental sustainability and creating harmony with nature. Conceptualizing a modern residential house with typical archipelago architecture is not only about beauty, but also about functionality, cultural preservation, and responsibility for the environment. This approach offers a blend of modern conveniences and local wisdom that has proven effective over the centuries. The concept of a modern residence with traditional Balinese architecture combines contemporary elements with local Balinese wisdom, creating a harmonious residential atmosphere between tradition and modernity. The research method used to examine the concept of traditional Balinese architecture requires a comprehensive approach, considering that this architecture is very rich in cultural, spiritual, social, and environmental values. The results of this study are: The concept of using guardrails and vegetation that is quite dense in terms of function to reduce the source of noise from outside the site and inside the site. The concept of building placement is in or away from the road. ; The use of vegetation can filter the air to cool so that it can affect the air conditioning in the building. ; Use of voids in Buildings. ; The Indonesian wind moves from the Southeast to the Northwest. ; Maximizing natural ventilation without compromising comfort in the building. ; The addition of a small canopy or tritisan as a barrier to sunlight that directly enters the building with later added curtains inside to reduce heat. ; The concept of circulation in this building is the main entrance which functions as an in-out vehicle. ; Drainage Creation in the house entrance area to accelerate the descent of rainwater. ; Rainwater reservoir by directing towards the front sewer. ; The concept of parking this building will be made one because it is considered for a private house.